Carl Olof Rosenius’ teologi med særligt henblik på hans kirkesyn - Kofod-Svendsen, Flemming (Dansk Teologisk Tidsskrift, 2016)
Carl Olof Rosenius, son of a vicar, grew up in Northern Sweden, where his family was active in a revival movement inspired by Lutheran theology. Early in life he decided to become a clergyman, but due to sickness and bad financial circumstances he never managed to complete his theological studies. He became a lay preacher and a very influential editor of the edifying magazine Pietisten [The Pietist]. Through this he became the spiritual leader of the emerging revival movement known as new evangelism. His theology was strongly influenced by Luther’s understanding of law and gospel. He had a particular spiritual gift to minister the gospel to awakened and seeking persons so they might come to live an evangelical Christian life. He wanted to promote a revival movement within the Swedish Church and rejected all separatism and the idea of forming a free church, just as he was against lay people’s celebration of Holy Communion. He rejected the incipient Baptist Movement and broke with Evangelical Alliance. Some of his disciples chose to form free churches.